Szkoła w Bizancjum w X wieku w świetle "Anonymi Professoris Epistulae" - Pakowski, Grzegorz (Vox Patrum, 2026)
Sources that allow for a reconstruction of the daily life of students and teachers in tenth-century Constantinople remain scarce. A notable exception is a collection of 122 letters preserved in a single codex at the British Library. Since the opening of the manuscript is missing and the remaining text lacks identifying details, the author is commonly referred to as the Anonymous Professor. His correspondence offers a window into his professional world: his interactions with students, disputes with rival teachers, dealings with imperial and Church dignitaries, and his constant struggle to secure a livelihood. This collection is an invaluable resource for understanding the era’s social fabric. Despite a critical edition, several studies, and a doctoral dissertation, the text has yet to be fully translated into any major language. By analyzing these letters, one can draw significant conclusions regarding the author’s work and the Byzantine educational system. This article aims to present these findings to a Polish audience.